Association of immune-mediated inflammatory diseases with depression and anxiety in patients with type 2 diabetes: A nationwide population-based study - Kwon, Oh Chan; Kim, Yuna; Chun, Jaeyoung; Han, Kyungdo; Park, Min-Chan; Kim, Ryul; Kim, Jie-Hyun; Youn, Young Hoon; Park, Hyojin (Frontiers in Medicine, 2023)
Objective Patients with type 2 diabetes (T2DM) are at a high risk of developing depression and anxiety. To better stratify the risk, we aimed to assess whether the presence of immune-mediated inflammatory diseases (IMIDs) confers a higher risk of depression and anxiety in these patients. Methods Patients with T2DM without prior depression or anxiety who underwent national health examination between 2009 and 2012 (n = 1,612,705) were enrolled from the nationwide health check-up data from Korean National Health Insurance Service. The outcome events were incident depression and anxiety, defined as International Classification of Diseases, 10th Revision codes F32–F33 and F40–F41, respectively. Multivariable Cox proportional hazard regression analyses were conducted to estimate the adjusted hazard ratio (aHR) and 95% confidence interval (CI) according to the existence of IMIDs. Results Over an average follow-up time of 6.4 years, existence of gut IMIDs was associated with a higher risk of depression (aHR: 1.28 [95% CI: 1.08–1.53]) and anxiety (1.22 [1.06–1.42]). Existence of joint IMIDs was associated with a higher risk of depression (1.34 [1.31–1.37]) and anxiety (1.31 [1.29–1.34]). Existence of skin IMID was associated with a higher risk of depression (1.18 [1.14–1.23]) and anxiety (1.13 [1.09–1.16]). The effect sizes of IMIDs on depression and anxiety were larger in those with ≥ 2 IMIDs (1.42 [1.19–1.69] and 1.49 [1.29–1.72], respectively) than in those with one IMID (1.30 [1.27–1.32] and 1.26 [1.24–1.28], respectively). Conclusion In patients with T2DM, presence of IMIDs was associated with a higher risk of depression and anxiety. More stringent attention and screening for anxiety and depression should be encouraged in patients with T2DM and comorbid IMIDs due to clinical implications of psychological distress on patient-reported outcomes and prognosis.